Химия пәні бойынша олимпиадаға арналған кейбір тәжірибелік есептердің шығару жолдары - Мендалиева, Д.К.; Жұмағалиева, Б.М. (My University, 2013)
The article considers the ways of solving some tasks in Chemistry, proposed in the experimental round of the Olympics.